Transcriptional and metabolic responses of apple to different potassium environments - Sun, Tingting; Zhang, Junke; Zhang, Qiang; Li, Xingliang; Li, Minji; Yang, Yuzhang; Zhou, Jia; Wei, Qinping; Zhou, Beibei (Frontiers in Plant Science, 2023)
Potassium (K) is one of the most important macronutrients for plant development and growth. The influence mechanism of different potassium stresses on the molecular regulation and metabolites of apple remains largely unknow. In this research, physiological, transcriptome and metabolite analyses were compared under different K conditions in apple seedlings. The results showed that K deficiency and excess conditions influenced apple phenotypic characteristics, soil plant analytical development (SPAD) values and photosynthesis. The hydrogen peroxide (H2O2) content, peroxidase (POD) activity, catalase (CAT) activity, and abscisic acid (ABA) content and indoleacetic acid (IAA) content, were regulated by different K stresses. Transcriptome analysis indicated that there were 2409 and 778 differentially expressed genes (DEGs) in apple leaves and roots under K deficiency conditions in addition to1393 and 1205 DEGs in apple leaves and roots under potassium excess conditions, respectively. KEGG pathway enrichment showed that the DEGs were involved in flavonoid biosynthesis, photosynthesis and plant hormone signal transduction metabolite biosynthetic processes in response to different K conditions. There were 527 and 166 differential metabolites (DMAs) in leaves and roots under low K stress as well as 228 and 150 DMAs in apple leaves and roots under high K stress, respectively. Apple plants regulate carbon metabolism and the flavonoid pathway to respond to low K and high K stresses. This study provides a basis for understanding the metabolic processes underlying different K responses and provides a foundation for improving the utilization efficiency of K in apples.